PENGARUH PENDIDIKAN, PENDAPATAN PERKAPITA DAN JUMLAH PENDUDUK TERHADAP KEMISKINAN DI PROVINSI JAWA TIMUR - Elda Wahyu Azizah; Sudarti Sudarti; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2018)
This research entitled "The Influence of Education, Income Per Capita and Population Against Poverty in East Java Province". This study aims to find out how the influence of education, per capita income and population on poverty in East Java Province. Method of data analysis tool used in this research is panel data regression analysis. The results of this study indicate that Education has a negative and significant effect on Poverty District and City of East Java Province. With a probability value of 0.0000 <α = 0.10 and t-count -15.35144 <t-table 2.02439. Income per capita has a negative and significant effect on Poverty District and City of East Java Province. With the probability value 0.0903 <α = 0.10 and t-count -1.702527 <t-table 1.28612. Number of Population has positive and significant influence to Poverty of Regency and City of East Java Province. With a probability value of 0.0000 <α = 0.10 and t-count 47.34174> t-table 1.28612.Keywords: Education, Income Per Capita, Population, Poverty